OPTIMALISASI PARAMETER SEGMENTASI UNTUK PEMETAAN LAHAN SAWAH MENGGUNAKAN CITRA SATELIT LANDSAT (STUDI KASUS PADANG PARIAMAN, SUMATERA BARAT DAN TANGGAMUS, LAMPUNG) - Parsa, I Made (Institut Teknologi Sepuluh Nopember, 2013)
Pixel-based digital-image classification results often contain of salt and pepper effects, while the visual classification has weakness because frequently provide inconsistent results. Due to the above, this study describes